Seren Taun: Public Communication and Survival Living Sunda Wiwitan - Alfonsus Sutarno Sutarno (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2023)
Abstract The stigma against local religions as heretical teachings and non-official state religion has resulted in their existence being always faced various existential challenges. It is the experience of the local religion of Sunda Wiwitan in Cigugur, Kuningan, West Java, the case study of this research. It was forced to disband twice in the past. It was a tragic event that Sunda Wiwitan did not expect again. Therefore, the local religion which was formerly known as the Javanese Sundanese Religion (ADS) must find the appropriate strategy for its existence in order to survive. This ethnographic study describes the significance of the Sérén Taun ceremony for the existence of Sunda Wiwitan. The thanksgiving ceremony for the harvest, for Sunda Wiwitan, is not just a cultural representation of the Sundanese agrarian society. It is mainly as a strategy for survival, a medium for criticism and resistance, as well as a form of public communication regarding its existence. The ceremony, which is full of moral and cultural values from the Sundanese ethnic community, is a way of how Sunda Wiwitan is inclusive of the socio-cultural life in which it is located. The state's appreciation of Sérén Taun by making it an Intangible Cultural Heritage and the involvement of the community in every Sérén Taun ceremony is a sign that Sunda Wiwitan is increasingly being recognized and appreciated. Now the Sérén Taun ceremony is a prototype of how other local religions can survive by exploring and strengthening their roots, namely culture.